Pengaruh Pemberian Minuman Kunyit dan Jahe Terhadap Penurunan Intensitas Dismenore dengan Riwayat Keluarga Sebagai Variabel Moderating - Budiani, Rhegita; Wijayanti, Wijayanti; Astuti, Hutari Puji (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2025)
Background: Dysmenorrhea is a common complaint among adolescent girls and can disrupt daily activities. Non-pharmacological therapies, such as ginger and turmeric drinks, are an alternative to reduce dysmenorrhea, and family history is suspected to influence its intensity.Objective: To determine the effect of ginger and turmeric drinks on reducing the intensity of dysmenorrhea, with family history as a moderating variable.Method: This quasi-experimental pretest–posttest study involved 66 adolescent girls with primary dysmenorrhea selected using purposive sampling. Dysmenorrhea intensity was measured using the Numeric Rating Scale (NRS), and family history was collected through interviews. Data were analyzed using Wilcoxon, Mann–Whitney tests, and moderation regressionResults and Discussion: Asymp test results showed that ginger and turmeric drinks reduced dysmenorrhea. Linear regression indicated that family history acted as a moderating variableConclusion: Ginger and turmeric drinks effectively relieve dysmenorrhea symptoms, with family history influencing the magnitude of the intervention effect.